Specific ranges of anti-Mullerian hormone and antral follicle count correlate to provide a prognostic indicator for IVF outcome - Keane, Kevin; Cruzat, Vinicius; Wagle, S.; Chaudhary, N.; Newsholme, Philip; Yovich, John (2016)
Advanced female age correlates with reduced ovarian reserve (OR) and is the primary factor underlying the limitation of success rates in Assisted Reproductive Technology (ART). Currently, predicted ovarian response to gonadotrophin stimulation is determined using transvaginal ultrasound to measure antral follicle count (AFC), an indirect measure of OR. However, assessing the level of anti-Mullerian hormone (AMH) has more recently been shown to correlate with OR, and its application has been adopted widely. This retrospective study was designed to determine the relationship between novel ranges of AMH and AFC in patients undergoing ART. There was a positive correlation between AMH and AFC category (r = 0.458, P < 0.01), with an 87% linear concordance observed for specific AFC ranges and mean serum AMH levels. Both OR markers were inversely correlated with female age (r = -0.428 and r = -0.392, respectively). Pregnancy and live birth rates were influenced by both AMH (P < 0.05) and AFC categories (P < 0.05). Conversely, miscarriage rates appeared to be more dependent on AFC categories (P < 0.05), but even more reliant on female age. Finally, the number of oocytes collected was positively correlated with AMH and AFC grading, while oocyte and embryo utilization rates were negatively correlated. Overall, both OR markers were positively and strongly related with each other, and when individual AMH readings were categorised into specific novel ranges, they demonstrated a more robust correlation with AFC groupings. Taken together, applying patient AMH within specific ranges may lead to a better estimation of OR and IVF outcomes.